Effects on resident work hours, sleep duration, and work experience in a randomized order safety trial evaluating resident-physician schedules (ROSTERS). Issue 8 (20th May 2019) - Barger, Laura K; Sullivan, Jason P; Blackwell, Terri; O'Brien, Conor S; St. Hilaire, Melissa A; Rahman, Shadab A; Phillips, Andrew J K; Qadri, Salim; Wright, Kenneth P; Segar, Jeffrey L; McGuire, John K; Vitiello, Michael V; et al.
Abstract: Study Objectives: We compared resident physician work hours and sleep in a multicenter clustered-randomized crossover clinical trial that randomized resident physicians to an Extended Duration Work Roster (EDWR) with extended-duration (≥24 hr) shifts or a Rapidly Cycling Work Roster (RCWR), in which scheduled shift lengths were limited to 16 or fewer consecutive hours. Methods: Three hundred two resident physicians were enrolled and completed 370 1 month pediatric intensive care unit rotations in six US academic medical centers. Sleep was objectively estimated with wrist-worn actigraphs. Work hours and subjective sleep data were collected via daily electronic diary. Results: Resident physicians worked fewer total hours per week during the RCWR compared with the EDWR (61.9 ± 4.8 versus 68.4 ± 7.4, respectively; p < 0.0001). During the RCWR, 73% of work hours occurred within shifts of ≤16 consecutive hours. In contrast, during the EDWR, 38% of work hours occurred on shifts of ≤16 consecutive hours. Resident physicians obtained significantly more sleep per week on the RCWR (52.9 ± 6.0 hr) compared with the EDWR (49.1 ± 5.8 hr, p < 0.0001). The percentage of 24 hr intervals with less than 4 hr of actigraphically measured sleep was 9% on the RCWR and 25% on the EDWR ( p < 0.0001). Conclusions: RCWRs were effective in reducing weekly work hours and the occurrence of >16 consecutive hour shifts, and improving sleep duration of resident physicians. Although inclusion of the six operational healthcare sites increases the generalizability of these findings, there was heterogeneity in schedule implementation. Additional research is needed to optimize scheduling practices allowing for sufficient sleep prior to all work shifts. Clinical Trial: Multicenter Clinical Trial of Limiting Resident Work Hours on ICU Patient Safety (ROSTERS), https://clinicaltrials.gov/ct2/show/NCT02134847